ANALISIS PERBEDAAN KARAKRERISTIK AIR DAN TEMUAN LARVA AEDES SP PADA KONTAINER DI DAERAH ENDEMIS DAN NON ENDEMIS DBD DI KOTA SEMARANG - Budiyono, Budiyono (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2010)
Environmental factors such as micro-water pH, salinity, temperature, nutrients (such as residual organic matter / decomposition of leaves, moss) has an important role in the proliferation of Aedes larvae Sp. Characteristics of water for the local microenvironment to one another have different characteristics, thus the microenvironment characteristics of the watet associated with the growth of larvae of Aedes sp to proliferate. This study aims to determine differences in microenvironment characteristics of the water container (tub) in non-endemic areas and endemic areas. The study was observational with cross sectional approach. The samples were 100 houses in endemic areas and 100 homes in non-endemic areas. Different characteristics were tested using unpaired t-test. The mean pH of the bath water in non-endemic areas in endemic areas 7.019 and 6.755 (p = 0.007), mean salinity of the water bath in non-endemic area 2.872 0/00 and 0.380 0/00  in endemic areas (p = 0.0001), mean temperature water bath in a non endemic area 29.59 °C and in endemic 26.17 °C (p = 0.189), average volume of water in bathtub non endemic 0.46415 m3. in endemic areas and 0.34757 m3 (p = 0.335). houses positive larvae in endemic areas of 43 homes found (43%) and positive home larvae in non-endemic area of 0 alias not found. Conclusion there are differences in the characteristics of the bath water in the area of non-endemic and endemic, for the parameters pH and slinity. The number of positive larvae findings in endemic areas is higher than non-endemic areas.